Compliance to prevention of alcohol and tobacco use as a risk factor of recurrent myocardial infarction - Sitovskyi, Andrii М.; Yakobson, Olena О.; Ulianytska, Nataliia YA.; Lavryniuk, Volodymyr E.; Gayduchik, Petro D. (My University, 2022)
Compliance to treatment is an important condition of treatment quality and effectiveness. Tobacco consumption has been recognized as one of the leading causes of health loss and premature death in both economically developed countries and developing ones.
Keywords: cardiac rehabilitation; preventive medicine; bad habits